1999
DOI: 10.1128/mcb.19.5.3485
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Cross Talk between NF-κB and p53

Abstract: Many cellular stimuli result in the induction of both the tumor suppressor p53 and NF-B. In contrast to activation of p53, which is associated with the induction of apoptosis, stimulation of NF-B has been shown to promote resistance to programmed cell death. These observations suggest that a regulatory mechanism must exist to integrate these opposing outcomes and coordinate this critical cellular decision-making event. Here we show that both p53 and NF-B inhibit each other's ability to stimulate gene expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
441
6
5

Year Published

2001
2001
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 556 publications
(478 citation statements)
references
References 85 publications
26
441
6
5
Order By: Relevance
“…Thus, whereas p53 may have some impact on expression of TMS1, it may be indirect. Alternatively, the regulation of TMS1 by genotoxins may involve transcriptional crosstalk between p53 and NF-kB (Webster and Perkins, 1999) as has been described for other pro-apoptotic NF-kB target genes, such as DR5 (Shetty et al, 2005).…”
Section: Discussionmentioning
confidence: 93%
“…Thus, whereas p53 may have some impact on expression of TMS1, it may be indirect. Alternatively, the regulation of TMS1 by genotoxins may involve transcriptional crosstalk between p53 and NF-kB (Webster and Perkins, 1999) as has been described for other pro-apoptotic NF-kB target genes, such as DR5 (Shetty et al, 2005).…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, the tumor suppressor menin, which is mutated/deleted in parathyroid tumors, was reported to bind and suppress NF-kB activation (Heppner et al, 2001). Regarding the tumor suppressor p53, it was reported that p53 generally inhibits NF-kB function, and vice versa (Webster and Perkins, 1999); however, more complex relationships between p53 and NF-kB have emerged (see below).…”
Section: Inhibition Of Nf-jb By Tumor Suppressorsmentioning
confidence: 99%
“…Two schools exist, one claiming that p53 is a prerequisite for NF-kB induction and that p53-induced NF-kB activation plays a merely apoptotic role, 64,65 the other claiming that genotoxic stress-induced p53 and NF-kB activation represent two independent parallel pathways, both activated by ATM, which might however interfere with each other's action through distinct mechanisms. 42,66,67 The first argument is based on the fact that some authors showed that the p53-null tumour cell line Saos-2 is resistant to doxorubicin or etoposideinduced NF-kB activation, while doxocycline-induced expression of p53 restores NF-kB activation. 65 The other school claims that p53-null cells such as Saos-2 or 10(1) murine embryo fibroblasts do activate NF-kB as efficiently as p53 wt cells in response to genotoxic stress.…”
Section: Ck2 and Friends: The Ikk-independent Pathwaysmentioning
confidence: 99%